Credit risk gap analysis for business loan expansion of pt. Bank sulutgo - Istar, Mario; Kaderi Wiryono, Sudarso (The Indonesian Journal of Business Administration, 2018)
Abstract. In order to become competitive, strong and give more economic contribution to regional growth, The Financial Service Authority of Indonesia (OJK) in 2015 launched Regional Development Bank (BPD) Transformation Program. OJK together with Association of Regional Development Bank (ASBANDA) have set up framework that conveys a holistic and balanced between business aspect, risk, and supporting foundation. BPD Transformation Program has vision, “To become highly competitive bank, strong, and significantly give contribution to equitable and sustainable regional economic growth”. In order to achieve such goals, there are few basis problems to be managed structurally, they are: (1) low contribution to local economy due to low rates of productive credit (business loan) with market share only 26% all BPDs (74% are other banks), (2) insufficient of good governance, human resources, risk management, and infrastructure that triggered the increasing of Non-Performing Loan (NPL) of productive credit segment. PT. Bank SulutGo (BSG), as one of the regional development banks has the obligation and responsibility to follow the program. One of the main issues that arises is portfolio management. BSG’s portfolio mainly are consumptive credit (90%) with small number of productive credit (10%), therefore the bank is exposed to credit risk. Through qualitative approach done by interview and questionnaire, this study aims to find the root cause why is it the business loan rate is low. In addition, the author conducts GAP analysis focus on credit risk to find answers and purpose solution for BSG to expand the segment. The result of the study suggests that the bank has to focus to prepare three aspects, they are: (1) Raising Core Capital, (2) Modernize integrated IT&IS infrastructure and (3) Develop HR (human resources development. Additionally, from seven categories of GAP analysis, BSG has to put more attention on operational activities, adequate credit risk control, credit risk and credit risk mitigation as priority 1 (most important) to be coped. Secondly, the bank has sufficient measurement and monitoring process and credit rating, therefore it should be priority 2 (important). Finally, due to well established risk awareness within BSG, culture building of the bank should be put last priority 3 (less important).Keywords: credit risk, GAP analysis, business loan, regional development bank, economic contribution.